To solve the equation \( 3\sqrt{x} + 12 = x + 8 \), we first isolate the square root term.
-
Subtract 12 from both sides:
\[ 3\sqrt{x} = x + 8 - 12 \]
This simplifies to:
\[ 3\sqrt{x} = x - 4 \]
-
Next, to eliminate the square root, divide both sides by 3:
\[ \sqrt{x} = \frac{x - 4}{3} \]
-
Now we square both sides to remove the square root:
\[ x = \left(\frac{x - 4}{3}\right)^2 \]
-
Expanding the right side:
\[ x = \frac{(x - 4)(x - 4)}{9} = \frac{x^2 - 8x + 16}{9} \]
-
To eliminate the fraction, multiply both sides by 9:
\[ 9x = x^2 - 8x + 16 \]
-
Rearranging the equation gives:
\[ x^2 - 8x - 9x + 16 = 0 \]
This simplifies to:
\[ x^2 - 17x + 16 = 0 \]
-
Next, we can factor this quadratic equation:
\[ (x - 1)(x - 16) = 0 \]
-
Setting each factor equal to zero gives us potential solutions:
\[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \]
\[ x - 16 = 0 \quad \Rightarrow \quad x = 16 \]
Now we have the potential solutions \( x = 1 \) and \( x = 16 \). We need to check these for extraneous solutions by substituting them back into the original equation.
Checking \( x = 1 \):
Substituting into the original equation:
\[ 3\sqrt{1} + 12 = 1 + 8 \]
This simplifies to:
\[ 3(1) + 12 = 1 + 8 \quad \Rightarrow \quad 3 + 12 = 9 \]
This is not true, so \( x = 1 \) is an extraneous solution.
Checking \( x = 16 \):
Substituting into the original equation:
\[ 3\sqrt{16} + 12 = 16 + 8 \]
This simplifies to:
\[ 3(4) + 12 = 16 + 8 \quad \Rightarrow \quad 12 + 12 = 24 \]
This simplifies to:
\[ 24 = 24 \]
This is true, so \( x = 16 \) is a valid solution.
Conclusion:
The only solution to the equation \( 3\sqrt{x} + 12 = x + 8 \) is
\[ \boxed{16} \]
No extraneous solutions are present other than \( x = 1 \).